The impact of bilingualism in within-language conflict resolution: an ERP study - Andras, Filip; Ramos, María Ángeles; Macizo, Pedro (Frontiers in Psychology, 2023)
We compared Spanish (L1)–English (L2) bilinguals and Spanish monolinguals in a semantic judgment relationship task in L1 that produced within-language conflict due to the coactivation of the two meanings of a Spanish homophone (e.g., “hola” and “ola” meaning “hello” and “a wave” in English). In this task, participants indicated if pairs of words were related or not (“agua-hola,” “water-hello”). Conflict arose because a word (“agua,” “water”) not related to the orthographic form of a homophone (“hola,” “hello”) was related to the alternative orthographic form (“ola,” “wave”). Compared to a control condition with unrelated word pairs (“peluche-hola,” “teddy-hello”), the behavioral results revealed greater behavioral interference in monolinguals compared to bilinguals. In addition, electrophysiological results revealed N400 differences between monolinguals and bilinguals. These results are discussed around the impact of bilingualism on conflict resolution.